When Generative AI Becomes a Colleague: Managers Making Sense of AI Advice at Work - Bajramovic,Almir; Saleh,Samar (2026)
Abstract Title: When Generative AI Becomes a Colleague: Managers Making Sense of AI Advice at Work Authors: Bajramović, Almir; Saleh, Samar Submission Date: 27th of May, 2026 Word Count: 21 238 Supervisor: Sverre Spoelstra Aim: This study explores how managers interpret, evaluate and integrate Generative AI (GenAI) as a source of advice in their day-to-day work. As GenAI becomes more embedded in organizational contexts, the study identifies a need to better understand how managers make sense of AI-generated suggestions in situations characterized by ambiguity, time pressure and uncertainty. Methodology: In this qualitative study, we adopt an abductive approach within an interpretivist framework. Seven semi-structured interviews were conducted with managers from different organizational contexts who actively used GenAI in their professional work. We have analyzed empirical material through the lens of sensemaking theory, with a specific focus on extracted cues, plausibility, identity construction and social context. Contributions: Our study demonstrates how AI-generated advice becomes embedded within managerial interpretation and judgment rather than functioning only as external decision support. The study further shows how AI-generated formulation shapes managerial reasoning, influencing how organizational situations are understood before decisions are consciously evaluated. The study therefore contributes to advice-taking and managerial sensemaking literature by arguing that AI-generated formulation itself can function as a form of advice before decisions are consciously evaluated. Keywords: Generative AI, managerial sensemaking, AI-generated advice, formulation, plausibility, managerial judgment, AI-supported managerial work
Keywords: Keywords: Generative AI; managerial sensemaking; AI-generated advice; formulation; plausibility; managerial judgment; AI-supported managerial work